Should Colorectal Cancer Screening in Portugal Start at the Age of 45 Years? A Cost-Utility Analysis - Currais,Pedro (2021)
Abstract: Background and Objective: Colorectal cancer (CRC) is one of the most common cancers in Europe. Recently, new data from the USA and Europe revealed an increase in the incidence of CRC in individuals aged <55 years and a reduction in those aged >65 years. Mortality rate was stable in patients aged <55 years and decreased after the age of 55 years. Based on the USA data, the American Cancer Society (ACS) published a qualified recommendation advocating the start of CRC screening at the age of 45 years. We aimed to evaluate if the changes in the CRC incidence/mortality observed in the USA and the rest of Europe also occur in Portugal, and then perform a cost-utility analysis of CRC screening that starts at 45 years of age. Methods: We evaluated the incidence of CRC by age group using data from the National Cancer Registry, and the mortality rate according to the National Statistics Institute in the periods 1993-2010 and 2003-2016. A cost-utility analysis was performed with a decision tree from a societal perspective comparing biennial fecal immunochemical test (FIT) or a single colonoscopy screening versus nonscreening at the age of 45 years in Portugal. Results: In Portugal, in 1993-2010, there was an increase in CRC incidence of 17% (from 25 to 30/100,000), 35% (from 39 to 54/100,000), and 71% (from 52 to 97/100,000) in patients aged 45-49 years, 50-54 years, and 55-59 years, respectively. The mortality rate of patients aged 45-54 years remained stable between 2003 and 2016 (12/100,000) as a counterpoint to a moderate decrease in those aged 55-64 years (from 38 to 35/100,000) and a sharp reduction in those aged 65-75 years (from 93 to 75/100,000). Screening for CRC at the age of 45 years has no cost utility with the current incidence. FIT screening provided an ICUR of EUR 84,304/quality-adjusted life years (QALY) while colonoscopy provided an ICUR of EUR 3,112,244/QALY. On one-way sensitivity analysis, FIT screening would only have cost utility at the present cost of colonoscopy under sedation (EUR 150) and acceptance rates if the incidence rate rises above 47.5/100,000; colonoscopy at this age would have no cost utility despite changes in costs and/or incidence rates. Conclusion: In Portugal, the incidence of CRC in patients aged 45-55 years has been increasing with a stable mortality rate, in contrast to the decrease in mortality in the age groups covered by the current CRC screening program. However, at present, CRC screening in Portugal at the age of 45 years has no cost utility and will only have this if the incidence rate rises above 47.5/100,000 (vs. the actual incidence of 30/100,000).